Peran Masyarakat dalam Pencapaian Millenium Development Goals 2015 dan Tantangan Pasca 2015: Studi 8 Kabupaten Indonesia - Donatus Klaudius Marut; Geradi Yudhistira (Bina Nusantara University, 2015)
In September 2000, the United Nations General Assembly adopted a declaration called Millennium Declaration, which has been detailed down into goals and targets of what is well-known as Millennium Development Goals (MDGs). Indonesia has committed to achieve MDGs. Until 2010 the MDGs achievements for Indonesia have been identified as mostly off-the-track. Some districts, however, have shown significant achievements and the processes of the achievements are worth noted. The process of MDGs achievements need special emphasis since this can become foundation for MDGs achievements and for sustainable performance in the districts. This paper analyzes roles of different stakeholders, including local communities, in 8 districts/cities in 8 provinces. There are success stories that are recommended to be replicated to other districts/cities in Indonesia.